Conventional bicortical pin substitution with a novel unicortical pin in external fixation: A biomechanical study. Issue 7 (July 2021) - Park, Kyeong-Hyeon; Park, Ho-Won; Oh, Chang-Wug; Lee, Jin-Han; Kim, Joon-Woo; Oh, Jong-Keon; Park, Il-Hyung; Ha, Sung-Soo
Highlights: The novel unicortical pin has been developed to overcome complications of the conventional bicortical pin used for temporary external fixation. The unicortical pin significantly increased fracture stability under both axial compressive and torsional load testing. The unicortical pin may be considered an alternative option to obtain adequate stability when performing external fixation of fractures. Abstract: Introduction: As most patients with polytrauma or open fractures are converted from temporary external fixation to definite stabilization, the prevention of complications such as infection is especially important. To overcome the high risk of infection associated with the use of the conventional bicortical pin for temporary external fixation, the authors developed a novel unicortical pin and analyzed it in a biomechanical study. Methods: The unicortical pin consisted of an inner screw, purchasing the cortical bone, and an outer sleeve with 6 spikes. A bicortical pin was used for the purpose of comparison. A fracture gap model was stabilized using a monoplanar configuration. Both the unicortical pins (Uni group) and bicortical pins (Bi group) underwent axial compressive and torsional load testing using a servo-hydraulic testing machine. Stiffness, load to failure, and mode of failure were documented. Results: Stiffness and load to failure of the Uni group (average, 40.5 N/mm and 1098.4 N, respectively) were greater than that of the Bi group (average, 33.7 N/mm and 968.6 N, respectively) in the axial compressive load test (P = 0.008 and 0.032). Stiffness and load to failure of the Uni group (average, 1.2 Nm/degree and 1.7 Nm, respectively) were also significantly higher than those of the Bi group (average, 0.8 Nm/degree and 0.6 Nm, respectively) in the torsional load test ( P  = 0.008 and 0.016). All pins in the Bi group were bent at the pin-synthetic bone interface without synthetic bone failure. Contrarily, the Uni group did not show any pin bending or failure. However, in the axial compression test, partial cracks in the synthetic bone were found at the interface with spikes in the outer shell. In addition, in the torsion test, incomplete fractures were seen through the inner screws' holes. Conclusion: Compared with the conventional bicortical pin, the newly designed unicortical pin significantly increased fracture stability under both axial compressive and torsional loads. The unicortical pin can be considered an alternative biomechanical solution to obtain adequate stability when performing external fixation of fractures.